The Reception and Canonisation of Minhāǧ al-ṭālibīn on the Swahili Coast in the 19th and 20th Centuries - Noor, Mohamed Aidarus (Arabica, 2025)
On the Swahili coast of the Indian Ocean world, Minhāǧ al-ṭālibīn has long been used as teaching material in madrasas and as a reference material for scholars, as well as in the qādīs’ courts. However, few scholars have investigated the phenomenon of textualization in the Šafiʿīte tradition on the Swahili coast despite its extended presence in the region. This article examines the reception of Minhāǧ al-tālibīn on the Swahili coast and argues why it is considered canonical and remained stable in its canonical status despite an avalanche of social, economic, technological, and political changes during the nineteenth and twentieth centuries. In investigating this process, the article will target questions of the selection and validation of legal texts, the actors and participants involved, and the role of muḫtaṣarāt (abridgements), such as Minhāǧ al-ṭālibīn, in understanding the construction of boundaries of canonicity. The premise for the canonical status of Minhāǧ al-ṭālibīn is based on the frequency mechanism, as determined through quantitative analysis, and the utility of legal texts as instructional manuals.